(3EOGQI GdeGd GdYGe s - (3QJjHI(B, (3WjHjs ((3YeGf(B:s (3OGQ GdEYUGQ GdYdej ddfTQ hGdJhRjY (B,s, 2016)
(3jVe eQGMd JWhQ GdEOGQI GdeGdjI hGcJSGH GdeGd aj GdbGfhf GdEOGQj, GdeGdjI GdYGeI hGdCKGQ GdeHGTQI ddEfaGb GdYGe, GdBKGQ GdEbJUGOjI ddbQhV GdYGeI, GdaSGO GdEOGQj hGdeGdj, eZdhWGJ GdeGd GdYGe hGdOjf GdYGe(B.s
(3HHdjhZQGajG(B: (3U(B.299-307s
Keywords: (3GdEOGQI GdeGdjIs; (3GdCehGd(B-(3GdbWGY GdYGe s; (3GdeGdjI GdYGeIs